Ocean vessel special cable and preparation method thereof
By using two-component silicone rubber and linear low-density polyvinyl matrix, combined with alumina fibers and phosphate glass powder, electron beam irradiation crosslinking is carried out to form a refractory blended polymer material and cover the ship's cables, solving the problems of aging and damage of cables in high humidity and high heat environments, and achieving the effects of fire resistance, high temperature resistance and high service life.
Patent Information
- Application Number
- CN202510191817.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
Existing ship cables aging and damage in high humidity, high heat, and high salinity corrosion environments, resulting in navigation safety hazards. The metal sheath produces electrochemical reactions in seawater to accelerate steel corrosion and increase maintenance costs.
Two-component silicone rubber and linear low-density polyethylene are used as substrates, and pre-crosslinking is performed by 1,4-bis(tert-butylperoxyisopropyl)benzene and triallyl isocyanurate, alumina fibers and phosphate glass powder are added, electron beam irradiation crosslinking is performed to form a refractory blended polymer material, and the tin-plated conductor and shielding layer are coated.
The cable is refractory and high temperature stability in high temperature and fire environments, extends the service life of the cable, reduces maintenance costs, and improves the self-supporting performance and shape stability of the cable.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a special cable for ocean-going ships and a preparation method thereof. Background Art
[0002] With the continuous improvement of electrification and automation of naval ships, the planning and safe operation of power systems have become an important part of modern naval equipment. Various types of power cables and signal cables distributed inside and outside the ship are responsible for providing power supply and signal transmission for various electrical equipment on the ship.
[0003] Naval ships operate in harsh environments of high humidity, high heat, and high salinity corrosion all year round. Marine cables directly exposed to such harsh environments will gradually age or even be damaged. Cable aging is a major hidden danger that threatens the safety of ship navigation. In order to improve the reliability of ship electrical system operation, increase the service life of cables, and reduce the maintenance cost of equipment, a metal sheath made of copper alloy or zinc alloy is usually sheathed on the outside of the cable in the past. These two metal materials provide a certain protection for the cable, but these two alloys will produce electrochemical reactions with steel in seawater or high salinity environments, greatly accelerating the corrosion rate of steel, causing significant damage to the surface of the ship's steel structure, and increasing the maintenance cost of the weapon system; and because this hard metal cable sheath cannot fit well with the soft cable, the sealing effect is poor, and the protection function of the cable is reduced. At the same time, the metal sheath is heavy, which brings certain difficulties to the hull itself and installation and fixation.
[0004] The situation at sea is also exacerbated by the fact that even after subdivision, the source of the fire is often impossible to reach, even if repairs are attempted. The successful implementation of firefighting is hampered in particular by the general decline in crew numbers due to widespread automation today. And precisely in emergency situations, there is hardly any crew available to fight the fire, because other vital tasks need to be completed. And if the firefighting water is sprayed over too large an area and cannot be discharged to the outer bilge through scuppers and sluices, it may cause the ship to list dangerously. At first glance, cables seem to be unnoticeable system components, but as the "blood and nerves" of the ship, they are of decisive importance in their application. The example of the new generation of special cables shows that the safety factor can continue to be increased even today through the long-term use of advanced high-performance materials, so that defense capabilities can be maintained and lives can be saved in emergency situations. High-performance materials are highly safe in shipbuilding, they maintain the functioning of systems for longer in the event of a fire and help protect the ship and the crew. Summary of the invention
[0005] The object of the present invention is to provide a special cable for ocean-going ships and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a special cable for an ocean-going ship, comprising the following preparation steps: (1) Two-component silicone rubber, linear low-density polyethylene, 1,4-bis(tert-butylperoxyisopropyl)benzene and triallyl isocyanurate were mixed and melt pre-crosslinked, and then antioxidant 1010 and antioxidant 168 were added and blended for 10 minutes to obtain intermediate A; (2) Wrapping the intermediate A on a double roller with a roller gap of 1 to 4 mm, adding alumina fiber and phosphate glass powder in sequence, and mixing, and then cross-linking by electron beam irradiation to obtain a refractory blended polymer material; (3) The tinned conductor is coated with a fire-resistant blended polymer material with a thickness of 0.8 to 2 mm, and is covered with a shielding layer woven from tinned copper wire and a protective layer made of a fire-resistant blended polymer material to obtain a special cable for ocean-going ships.
[0007] Furthermore, the preparation method of the two-component silicone rubber in step (1) is as follows: vinyl silicone oil, hexamethyldisilazane, and deionized water are mixed in a mass ratio of 100:10-30:1-5, the temperature is raised to 100-160°C, and the mixture is stirred at 60-150 rpm for 20-50 min, white carbon black with a mass of 0.1-0.2 times that of the vinyl silicone oil is added, and the stirring is continued for 3-6 h to obtain a base material; the base material, vinyl silicone oil, and platinum catalyst are mixed in a mass ratio of 100:0.2-1:10. -5 Mix to obtain component A; mix the base material, hydrogen-containing silicone oil, ethynyl cyclohexanol, and vinyl tri-tert-butyl peroxysilane in a mass ratio of 100:0.5:0.01:0.1~0.5 to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone rubber.
[0008] Furthermore, the model of the linear low-density polyethylene in step (1) is DFDA-6101.
[0009] Furthermore, in step (1), the melting temperature is 140-190° C., the melting time is 10-30 min, and the melting speed is 60-120 rpm.
[0010] Furthermore, in step (1), the mass ratio of the two-component silicone rubber, linear low-density polyethylene, 1,4-bis(tert-butylperoxyisopropyl)benzene, triallyl isocyanurate, antioxidant 1010, and antioxidant 168 is 100:30~70:0.3~1.2:0.1~0.6:2:1.
[0011] Furthermore, the length of the alumina fiber in step (2) is 0.1-1 mm.
[0012] Furthermore, the mixing temperature in step (2) is 90-125° C. and the mixing time is 30-70 min.
[0013] Furthermore, the process parameters of the electron beam irradiation in step (2) are: irradiation energy of 1.5 MeV, and dose of 100-200 kGy.
[0014] Furthermore, in step (2), the mass ratio of the intermediate A, alumina fiber and phosphate glass powder is 80:10-20:15-30.
[0015] Furthermore, in step (3), the thickness of the shielding layer is 0.5-2 mm, and the thickness of the protective layer is 2-5 mm.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention uses two-component silicone rubber and linear low-density polyethylene as a matrix, and pre-crosslinks are performed by using a crosslinking agent 1,4-bis(tert-butylperoxyisopropyl)benzene and an auxiliary crosslinking agent triallyl isocyanurate. Under high temperature conditions, 1,4-bis(tert-butylperoxyisopropyl)benzene is homolytically split to generate alkoxy free radicals, and the alkoxy free radicals capture active hydrogen atoms from the silicone rubber, thereby improving the activity of the silicone rubber. Under the catalytic action of metal platinum, self-crosslinking occurs to form a high molecular polymer with dimethylsiloxane as the main chain, and physical crosslinks are formed with polyethylene linear macromolecules. Triallyl isocyanurate enhances the stability of the crosslinking structure through its triazine benzene ring structure, so that the matrix material is not easy to bend and collapse at high temperature, achieving fire resistance and high temperature resistance. Alumina short fibers are then added, and the fibers are uniformly dispersed in the matrix through a tensile force. In the process, the orderliness of the crosslinked macromolecular chains in the matrix is also improved. At the same time, phosphate glass is used as a flux. Under high temperature conditions, the fibers are uniformly dispersed in the matrix. In the state, the molten phosphate is in a glass liquid phase, filling the pores generated by the thermal decomposition of the polymer and connecting with the alumina phase. The aluminum phosphate crystal phase is generated through the phosphorus oxide in the phosphate glass powder. The generation of the crystalline phase can limit the fluidity of the molten glass liquid phase, thereby improving the self-supporting performance and shape stability of the matrix, and gradually forming a hard and dense porcelain shell on the surface, significantly reducing the thermal conductivity of the matrix, delaying the further decomposition of the internal polymer substances, and greatly improving the fire resistance and high temperature stability of the matrix. Finally, after radiation cross-linking, hydrogen bonds are formed between the molecular chains of the polymer and the silicone rubber to form a network structure, thereby increasing the binding force between the macromolecules, compensating for the side effects caused by the addition of fillers, thereby improving the tensile strength of the matrix material, and the polar groups generated by radiation improve the interface performance between the matrix and the filler. At the same time, triallyl isocyanurate undergoes a ring-opening reaction under the action of radiation to form an active bridge bond with the polymer, further improving the degree of cross-linking between the components, thereby increasing the fire resistance and high temperature resistance of the matrix material. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the special cables for ocean-going ships prepared in the following examples are as follows: High temperature resistance: The high temperature resistance effect of the embodiment and the comparative example of the same size was tested. After being placed at 150°C for 100 hours, the tensile strength and elongation at break were tested in accordance with GB / T1040.
[0019] Fire resistance: The same size of the embodiment and the comparative example were tested for limiting oxygen index (LOI) according to GB / T2406.2.
[0020] Example 1; (1) Vinyl silicone oil, hexamethyldisilazane and deionized water were mixed in a mass ratio of 100:10:1, heated to 100°C, stirred at 60 rpm for 20 min, added with white carbon black 0.1 times the mass of vinyl silicone oil, and continued to stir for 3 h to obtain a base material; the base material, vinyl silicone oil and platinum catalyst were mixed in a mass ratio of 100:0.2:10 -5 Mix to obtain component A; mix the base material, hydrogenated silicone oil, ethynyl cyclohexanol, and vinyl tri-tert-butyl peroxysilane in a mass ratio of 100:0.5:0.01:0.5 to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone rubber; mix the two-component silicone rubber, linear low-density polyethylene DFDA-6101, 1,4-bis(tert-butylperoxyisopropyl)benzene, and triallyl isocyanurate, and perform melt pre-crosslinking. The temperature is 140°C, the time is 10 minutes, the rotation speed is 60 rpm, and then antioxidant 1010 and antioxidant 168 are added and blended for 10 minutes to obtain intermediate A; the mass ratio of the two-component silicone rubber, linear low-density polyethylene DFDA-6101, 1,4-bis(tert-butylperoxyisopropyl)benzene, triallyl isocyanurate, antioxidant 1010, and antioxidant 168 is 100:30:0.3:0.1:2:1; (2) Wrapping the intermediate A on a double roller with a roller gap of 1 mm, adding alumina fibers with a length of 0.1 mm and phosphate glass powder in turn, and mixing them at a temperature of 90°C for 30 min, and then electron beam irradiation cross-linking, the process parameters of which are: irradiation energy of 1.5 MeV, dose of 100 kGy, to obtain a refractory blended polymer material; the mass ratio of the intermediate A, alumina fibers with a length of 0.1 mm, and phosphate glass powder is 80:10:15; (3) The tinned conductor is coated with a fire-resistant blended polymer material with a thickness of 0.8 mm, and is covered with a shielding layer woven from tinned copper wire with a thickness of 0.5 mm and a protective layer made of a fire-resistant blended polymer material with a thickness of 2 mm, thereby obtaining a special cable for ocean-going ships.
[0021] Example 2; (1) Vinyl silicone oil, hexamethyldisilazane and deionized water were mixed in a mass ratio of 100:20:3, heated to 130°C, stirred at 100 rpm for 35 min, added with white carbon black 0.15 times the mass of vinyl silicone oil, and continued to stir for 4.5 h to obtain a base material; the base material, vinyl silicone oil and platinum catalyst were mixed in a mass ratio of 100:0.6:10 -5Mix to obtain component A; mix the base material, hydrogenated silicone oil, ethynyl cyclohexanol, and vinyl tri-tert-butyl peroxysilane in a mass ratio of 100:0.5:0.01:0.3 to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone rubber; mix the two-component silicone rubber, linear low-density polyethylene DFDA-6101, 1,4-bis(tert-butylperoxyisopropyl)benzene, and triallyl isocyanurate, and perform melt pre-crosslinking. The temperature is 165°C, the time is 20 minutes, the rotation speed is 90 rpm, and then antioxidant 1010 and antioxidant 168 are added and blended for 10 minutes to obtain intermediate A; the mass ratio of the two-component silicone rubber, linear low-density polyethylene DFDA-6101, 1,4-bis(tert-butylperoxyisopropyl)benzene, triallyl isocyanurate, antioxidant 1010, and antioxidant 168 is 100:50:0.7.2:0.4:2:1; (2) Wrapping the intermediate A on a double roller with a roller gap of 2.5 mm, adding alumina fibers with a length of 0.5 mm and phosphate glass powder in turn, and mixing them at a temperature of 112° C. for 50 min, and then electron beam irradiation cross-linking, the process parameters of which are: irradiation energy of 1.5 MeV, dose of 150 kGy, to obtain a refractory blended polymer material; the mass ratio of the intermediate A, alumina fibers with a length of 0.5 mm, and phosphate glass powder is 80:15:23; (3) The tinned conductor is coated with a fire-resistant polymer blend material with a thickness of 1.2 mm, and is covered with a shielding layer woven from tinned copper wire with a thickness of 1.1 mm and a protective layer made of a fire-resistant polymer blend material with a thickness of 3.5 mm, thereby obtaining a special cable for ocean-going ships.
[0022] Example 3; (1) Vinyl silicone oil, hexamethyldisilazane and deionized water were mixed in a mass ratio of 100:30:5, heated to 160°C, stirred at 150rpm for 50min, added with white carbon black 0.2 times the mass of vinyl silicone oil, and continued to stir for 6h to obtain a base material; the base material, vinyl silicone oil and platinum catalyst were mixed in a mass ratio of 100:1:10 -5Mix to obtain component A; mix the base material, hydrogenated silicone oil, ethynyl cyclohexanol, and vinyl tri-tert-butyl peroxysilane in a mass ratio of 100:0.5:0.01:0.5 to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone rubber; mix the two-component silicone rubber, linear low-density polyethylene DFDA-6101, 1,4-bis(tert-butylperoxyisopropyl)benzene, and triallyl isocyanurate, and perform melt pre-crosslinking. The temperature is 190°C, the time is 30 minutes, the rotation speed is 120 rpm, and then antioxidant 1010 and antioxidant 168 are added and blended for 10 minutes to obtain intermediate A; the mass ratio of the two-component silicone rubber, linear low-density polyethylene DFDA-6101, 1,4-bis(tert-butylperoxyisopropyl)benzene, triallyl isocyanurate, antioxidant 1010, and antioxidant 168 is 100:70:1.2:0.6:2:1; (2) Wrapping the intermediate A on a double roller with a roller gap of 4 mm, adding alumina fiber with a length of 1 mm and phosphate glass powder in turn, and mixing them at a temperature of 125° C. for 70 min, and then electron beam irradiation cross-linking, the process parameters are: irradiation energy of 1.5 MeV, dose of 200 kGy, to obtain a refractory blended polymer material; the mass ratio of the intermediate A, alumina fiber with a length of 1 mm, and phosphate glass powder is 80:20:30; (3) The tinned conductor is coated with a fire-resistant blended polymer material with a thickness of 2 mm, and is covered with a shielding layer woven from tinned copper wire with a thickness of 2 mm and a protective layer made of a fire-resistant blended polymer material with a thickness of 5 mm, thereby obtaining a special cable for ocean-going ships.
[0023] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: vinyl silicone oil, hexamethyldisilazane, and deionized water are mixed in a mass ratio of 100:20:3, heated to 130°C, stirred at 100rpm for 35min, added with white carbon black 0.15 times the mass of vinyl silicone oil, and continued to stir for 4.5h to obtain a base material; the base material, vinyl silicone oil, and platinum catalyst are mixed in a mass ratio of 100:0.6:10 -5Mix to obtain component A; mix the base material, hydrogen-containing silicone oil, ethynyl cyclohexanol, and vinyl tri-tert-butyl peroxysilane in a mass ratio of 100:0.5:0.01:0.3 to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone rubber; mix the two-component silicone rubber, linear low-density polyethylene DFDA-6101, and 1,4-bis(tert-butylperoxyisopropyl)benzene, and perform melt pre-crosslinking at a temperature of 165°C, a time of 20 minutes, and a speed of 90 rpm, and then add antioxidant 1010 and antioxidant 168, and blend for 10 minutes to obtain an intermediate A; the mass ratio of the two-component silicone rubber, linear low-density polyethylene DFDA-6101, 1,4-bis(tert-butylperoxyisopropyl)benzene, antioxidant 1010, and antioxidant 168 is 100:50:0.7.2:2:1; the remaining steps are the same as in Example 2.
[0024] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: wrapping the intermediate A on a double roller with a roller gap of 2.5 mm, adding phosphate glass powder, and mixing at a temperature of 112° C. for 50 min, and then electron beam irradiation cross-linking with process parameters of irradiation energy of 1.5 MeV and dose of 150 kGy to obtain a refractory blended polymer material; the mass ratio of the intermediate A to the phosphate glass powder is 80:23; the remaining steps are the same as Example 2.
[0025] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: wrap the intermediate A on a double roller with a roller gap of 2.5 mm, add alumina fibers with a length of 0.5 mm, and mix them at a temperature of 112° C. for 50 min, and then perform electron beam irradiation cross-linking. The process parameters are: irradiation energy of 1.5 MeV and dosage of 150 kGy, to obtain a refractory blended polymer material; the mass ratio of the intermediate A to the alumina fibers with a length of 0.5 mm is 80:15; the remaining steps are the same as Example 2.
[0026] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: wrap the intermediate A on a double roller with a roller gap of 2.5 mm, add alumina fibers with a length of 0.5 mm and phosphate glass powder in sequence, and mix them at a temperature of 112° C. for 50 min to obtain a refractory blended polymer material; the mass ratio of the intermediate A, alumina fibers with a length of 0.5 mm and phosphate glass powder is 80:15:23; the remaining steps are the same as Example 2.
[0027] Effect example Table 1 below shows the performance analysis results of special cables for ocean-going ships using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0028] Table 1
[0029] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses two-component silicone rubber and linear low-density polyethylene as a matrix, and pre-crosslinks are performed by a crosslinking agent 1,4-bis(tert-butylperoxyisopropyl)benzene and an auxiliary crosslinking agent triallyl isocyanurate. Under high temperature conditions, 1,4-bis(tert-butylperoxyisopropyl)benzene is homolytically split to generate alkoxy free radicals, and the alkoxy free radicals capture active hydrogen atoms from the silicone rubber, thereby improving the activity of the silicone rubber. While self-crosslinking occurs, physical crosslinks are formed with polyethylene linear macromolecules, and triallyl isocyanurate enhances the stability of the crosslinked structure through its triazine benzene ring structure, thereby achieving fire resistance and high temperature resistance. Alumina short fibers are then added, and the fibers are evenly distributed in the matrix through a tensile force. Dispersion, and at the same time using phosphate glass as a flux, at high temperature, fill the pores generated by the thermal decomposition of the polymer, and connect with alumina to generate aluminum phosphate crystal phase, thereby improving the self-supporting performance and shape stability of the matrix, and gradually forming a hard and dense porcelain shell on the surface, delaying the decomposition of internal polymer substances, greatly improving the fire resistance and high temperature stability of the matrix, and finally through radiation cross-linking, hydrogen bonds are formed between the molecular chains of the polymer and the silicone rubber to form a network structure, thereby compensating for the side effects caused by the addition of fillers, thereby improving the tensile strength of the matrix material, and the polar groups generated by irradiation improve the interface performance between the matrix and the filler, and at the same time, triallyl isocyanurate forms an active bridge bond with the polymer under the action of radiation, further enhancing the fire resistance and high temperature resistance of the matrix material.
[0030] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a special cable for an ocean-going ship, characterized in that: The method comprises the following preparation steps: (1) Two-component silicone rubber, linear low-density polyethylene, 1,4-bis(tert-butylperoxyisopropyl)benzene and triallyl isocyanurate were mixed and melt pre-crosslinked, and then antioxidant 1010 and antioxidant 168 were added and blended for 10 minutes to obtain intermediate A; (2) Wrapping the intermediate A on a double roller with a roller gap of 1 to 4 mm, adding alumina fiber and phosphate glass powder in sequence, and mixing, and then cross-linking by electron beam irradiation to obtain a refractory blended polymer material; (3) The tinned conductor is coated with a fire-resistant blended polymer material with a thickness of 0.8 to 2 mm, and is covered with a shielding layer woven from tinned copper wire and a protective layer made of a fire-resistant blended polymer material to obtain a special cable for ocean-going ships.
2. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: The preparation method of the two-component silicone rubber in step (1) is as follows: vinyl silicone oil, hexamethyldisilazane and deionized water are mixed in a mass ratio of 100:10-30:1-5, the temperature is raised to 100-160°C, and the mixture is stirred at 60-150 rpm for 20-50 min. White carbon black with a mass of 0.1-0.2 times of the mass of the vinyl silicone oil is added, and the mixture is stirred for 3-6 h to obtain a base material. The base material, vinyl silicone oil and platinum catalyst are mixed in a mass ratio of 100:0.2-1:
10. -5 Mix to obtain component A; mix the base material, hydrogen-containing silicone oil, ethynyl cyclohexanol, and vinyl tri-tert-butyl peroxysilane in a mass ratio of 100:0.5:0.01:0.1~0.5 to obtain component B; mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone rubber.
3. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: The model of the linear low-density polyethylene in step (1) is DFDA-6101.
4. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: The melting temperature in step (1) is 140-190° C., the melting time is 10-30 min, and the melting speed is 60-120 rpm.
5. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: The mass ratio of the two-component silicone rubber, linear low-density polyethylene, 1,4-bis(tert-butylperoxyisopropyl)benzene, triallyl isocyanurate, antioxidant 1010, and antioxidant 168 in step (1) is 100:30-70:0.3-1.2:0.1-0.6:2:
1.
6. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: The length of the alumina fiber in step (2) is 0.1-1 mm.
7. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: The mixing temperature in step (2) is 90-125° C. and the mixing time is 30-70 min.
8. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: The process parameters of the electron beam irradiation in step (2) are: irradiation energy of 1.5 MeV and dose of 100-200 kGy.
9. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: In step (2), the mass ratio of the intermediate A, alumina fiber and phosphate glass powder is 80:10-20:15-30.
10. The method for preparing a special cable for ocean-going ships according to claim 1, characterized in that: In step (3), the thickness of the shielding layer is 0.5-2 mm, and the thickness of the protective layer is 2-5 mm.
Citation Information
Patent Citations
Fire-proof power cable
CN103050178A
Fireproof cable
WO2023240892A1